Percurso formativo de docentes atuantes em um curso técnico: tecituras e caminhos percorridos no desenvolvimento profissional do professor técnico - Piovesan, Josiane Bertoldo (2020)
This dissertation is part of the research line: Teacher Training for Professional and Technological Education - LP2, Master's Program in Professional and Technological Education. The objective of this study was to verify the academic and professional trajectory of teachers linked to the Technical Course in Elderly Care of the Polytechnic College Federal University of Santa Maria (UFSM). The problem situation is related to the author's practical experience during her academic training in the Occupational Therapy Course. Therefore, with regard to teaching practice and its knowledge, the following questions were asked: how does the academic and professional trajectory of teachers linked to the Technical Course in Elderly Care take place? How do these professionals, who have not been trained for the teaching process, develop their teaching practice? It is assumed that teachers in the health area, as bachelors, do not have training for teaching. These, by the practical practice that the profession demands, are constituted as teaching professionals. The methodology is characterized as field research, through a qualitative approach, carried out based on the case study, at the Polytechnic College of UFSM. Data were collected through an electronic questionnaire sent to teachers working in the aforementioned technical course. The analysis of the results was made from the characterization of the narrative method, through the studies of Reissman (2008) and its conceptualization of thematic narrative analysis, which considers what is said and experienced (experienced during pedagogical practices) by the researcher. It is concluded, according to the data collected in the research, that the notices of entry to the teaching career should be more careful as to the requirement that the candidate has experience in teacher training or professional practice. It is observed that only one of the teachers interviewed had experienced prior to teaching and, thus, it is implied that the Polytechnic College may include in its pedagogical planning a pedagogical and academic training to its professionals. Therefore, it is noteworthy that the criterion of professional experience is important when choosing the candidate, that is, it is important to demand experience prior to teaching so that it defines a time of experience to ensure the quality in the training of new students. It is therefore hoped that this research will serve as a reflection for the Polytechnic College and the Federal University of Santa Maria, in order to rethink the upcoming teacher competitions because, according to the data evidenced in this study, it is perceived that the institution, when hiring a professional without experience, will automatically demand some investments in this teacher.